Urgensi Nafkah dalam Islam : Kajian Tematik Hadis Nafkah dalam Kitab Shahih Bukhara dan Musnad Imam Ahmad - Nurmakiyah Nurmakiyah; Syahmila Putri; Zikri Darussamin (Moral : Jurnal kajian Pendidikan Islam, 2025)
The provision of sustenance (nafaqah) is a crucial aspect of family life that is strongly emphasized in Islamic teachings. This study aims to explore the urgency of nafaqah through a thematic approach to authentic (ṣaḥīḥ) hadiths that address the obligation of financial support, viewed from legal, ethical, and social perspectives. Using the maudhū‘ī (thematic) method, this research collects and analyzes ṣaḥīḥ hadiths from major compilations such as Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim to gain a comprehensive understanding of Islamic principles regarding nafaqah. The findings reveal that providing sustenance is not only a legal duty of the husband, but also a sign of faith, compassion, and a means of maintaining social stability. This study highlights the importance of a proper understanding of nafaqah in Islam as a foundation for building a harmonious and God-pleasing family.